The experience of the ANGRA farmers in prolificacy improvement by the BMP15 ovine mutation FecxR in Rasa Aragonesa - Laviña A.; López M.; Monteagudo L.V.; Tejedor M.T.; Macías Á.; Martin E. (Innovation for sustainability in sheep and goats, 2019)
The FecXR mutation is a variant of the ovine gene BMP15 involved in the increase of prolificacy. It was found in the breed Rasa Aragonesa, and since 2007, the National Association of Breeders of this sheep (ANGRA) included it in its genetic selection scheme under the denomination “Gene Santa Eulalia” (or GASE). FecXR provides a sustainable molecular tool to improve productive efficiency avoiding additional treatments. Over 4000 ewes carrying this mutation are nowadays exploited by members of ANGRA. The positive effect of FecXR on prolificacy is well known, resulting in a clear improvement of incomes and cost effectiveness. This communication reports the results of a satisfaction survey conducted among 18 producers using FecXR in their flocks. The survey is based up on the farmers’ personal perception of different questions regarding the ewes carrying FecXR. The statistical analysis of data provides several conclusions about practical aspects that, prior to the diffusion of this variant, generated some doubt among producers. In fact, the producers do not observe differences among the FecXR carrier and wild type ewes as it refers to general management, even if most of them consider that the mutation provides a higher fertility, prolificacy and cost effectiveness. All of them should recommend the use of FecXR in other flocks in practice. A high degree of satisfaction with the use of FecXR is therefore observed, confirming the results of the objective analysis of the data actually recorded by the official Control of Productions.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)